ANALISIS EFEKTIVITAS PAJAK DAERAH, DERAJAT DESENTRALISASI FISKAL, DAN JUMLAH INDUSTRI TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA PROVINSI SULAWESI TENGGARA - Andi Nabila Aspasia; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to find out how much the effectiveness of local taxes and the degree of fiscal decentralization and the effect of the effectiveness of local taxes, the degree of fiscal decentralization, and the amount of industry to local revenue in the Regency / City of Southeast Sulawesi Province in 2012-2016. The analytical tools used are the analytical tools (1) the ratio of the effectiveness of local taxes (2) the degree of fiscal decentralization and (3) multiple linear regression analysis. The results of this study indicate, based on the average calculation of the effectiveness of tax collection of regencies / municipalities of Southeast Sulawesi province known the highest local tax effectiveness is in 2012 and the lowest in 2016. And based on the average calculation results of fiscal decentralization degree in the Regency / City Southeast Sulawesi Province is known that the highest fiscal decentralization degree is in 2012 and the lowest is in 2016. Based on the result of multiple linear regression test, it is known that the effectiveness of local tax has a significant positive effect on the local revenue (PAD), the degree of fiscal decentralization has a significant negative effect on the local revenue (PAD), and the number of industries has a significant positive effect on local revenue (PAD).Keywords: Local Tax Effectiveness, Degree of Fiscal Decentralization, Number of Industry, Local Original Income.